Emerging work environments in the pandemic era: a gendered approach to work-life balance programs - Sreya, B.; Lakshmana Rao, Ayyagari; Ramakrishnan, G.; Kulshretha, Nikhil (Frontiers in Sociology, 2023)
As the coronavirus pandemic affects virtually every sector of the economy, this ongoing review examines the effects of remote working on women's job performance—including hypotheses about serious activities and how they may balance work and family. In recent years, psychometric testing has become increasingly popular with organizations worldwide, and they are looking at this method to better understand how women achieve balance in their lives. The aim of this work is to investigate how different aspects of psychometrics and factors relating to work-life balance influence women's satisfaction levels. An exploratory factor assessment (EFA) and a confirmatory factor assessment (CFA) using a seven-point Likert scale were performed on data collected from 385 selected female IT workers whose satisfaction levels toward psychometric assessments in their organization were examined. The current study uses EFAs and CFAs to develop and identify the key factors in women's work-life balance. The results also showed that three significant variables accounted for 74% of the variance: 26% from work and family, 24% from personal factors, and 24% from loving their job.